The next frontier in tourism emotion research. Issue 12 (21st July 2019) - Moyle, Brent D.; Moyle, Char-lee; Bec, Alexandra; Scott, Noel
Abstract : Emotion is emerging as a central concept in tourism research, critical for the delivery of memorable tourism experiences. However, existing approaches in tourism do not adequately explain the process by which emotions are elicited. Recent advances in cognitive and neuropsychology demonstrate that emotions are elicited through an appraisal process, which occurs in the cortex of the brain. These processes produce chemical monoamine neurotransmitters that lead to bodily feelings, which in turn enable our brain to recognise emotions. This research note draws on Lövheim's Cube, a self-report scale that provides a proxy indicator of the likely presence of monoamine neurotransmitters of serotonin, dopamine and noradrenaline. Six images of the Great Barrier Reef were used as a stimuli in an online panel survey ( n = 1249). Results demonstrate that images used by tourism stakeholders are likely to produce stronger neurological reactions than images from an environmental non-governmental organisation. Combining recent advances in self-report methods with a neurocognitive approach has the propensity to offers additional insight into emotional reactions to visual stimuli. Further research should focus on the efficacy of utilising self-report measures with cutting edge psychophysiological techniques, such as ambulatory electroencephalography (EEG) to open the door to the next frontier in tourism emotion research.